A new voltammetric approach for the determination of β-carotene in vegetables and pharmaceutical capsules using a gold electrode - Jashari, Granit; Muriqi, Sali; Arbneshi, Tahir; Metelka, Radovan; Švancara, Ivan; Sýs, Milan (Talanta, 2021)
Significant improvements in the voltammetric determination of β-carotene (BCA) have been achieved, mainly by the replacement of toxic dichloromethane with acetone and using non-mercury electrode. The respective procedure is based on anodic oxidation of BCA at a gold electrode in the disc configuration, when using square-wave voltammetry in pure acetone (99.8%) with 0.1 mol L-1 LiClO4 as the supporting electrolyte. The method comprises extraction of the analyte from the sample with acetone, thus avoiding the usually used highly toxic solvents. Analytically, it can be characterized by a linear range from 6.0 × 10-6 to 5.9 × 10-4 mol L-1 with regression equation Ipa = 0.0184c -0.1631 and correlation coefficient, R2 = 0.9998, limits of detection and quantification LOD = 1.6 × 10-6 mol L-1 and LOQ = 5.4 × 10-6 mol L-1, respectively; both being obtained at a potential step of 5 mV, with the pulse amplitude of 25 mV, and a frequency of 80 Hz. After optimization, the method was evaluated in series of analyses; namely, with two samples of vegetables and two pharmaceutical preparations (capsules), when the results could be compared to those of a reference spectrophotometric method. Due to a simple instrumentation, including sample preparation, the voltammetric method for the determination of BCA can be recommended as a quick screening assay in food and pharmaceutical analysis.
Keywords: Square-wave voltammetry; Electrodes; Electrochemistry; beta Carotene; beta-karoten; elektrody; Gold; Capsules; tobolky; zlato; elektrochemie; Gold disk electrode; β-Carotene; Food and pharmaceutical samples; Vegetables; zelenina